EFFECTS OF MULTIMODAL INSTRUCTION ON STUDENTS' PERFORMANCE IN ENGLISH SPEAKING SKILLS AND SELF-EFFICACY IN COLLEGES OF EDUCATION, NORTH WEST ZONE, NIGERIA - Jamilu Sani; Sule Sale; Mustapha Shettima (English Education Program, Education Faculty, Universitas Nurul Huda, 2026)
This study investigated the effects of multimodal instruction on students’ performance in English speaking skills and self-efficacy in Colleges of Education, North West Zone, Nigeria. Quasi-experimental research was adopted involving the 2024/2025 registered 488 NCE 1 English language students of nine colleges of Education in the study area. Purposive sampling was used to select 4 out of the 9 colleges of Education with a total of 204 NCE 1 students as the sample size. Three sets of data were collected: pre-test, post-test and post-treatment self-efficacy data. These were analysed using One-Way ANOVA and descriptive statistics respectively. Results indicated significant improvements in English speaking skills. Mean scores rose from 2.543, 9.442, 9.915, 0.000 and 7.413 in pre-test to 1404.914, 885.219, 873.223, 1370.581 and 791.770 in post-test in terms of ESPS, ESSPS, EVPS, EGS and EFS, respectively. Further, subjects demonstrated higher degree of self-efficacy in English speaking skills after the treatment. It was concluded the improvements followed the series of multimodal trainings to which the learners were exposed involving linguistic and non-linguistic mode. Although limited in terms of scope and rating criteria, the study suggested adoption of wider scope and technology-informed rating criteria by future research.